2006
DOI: 10.1080/08927010600898862
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimates of environmental copper release rates from antifouling products

Abstract: The US Navy Dome method for measuring copper release rates from antifouling paint in-service on ships' hulls can be considered to be the most reliable indicator of environmental release rates. In this paper, the relationship between the apparent copper release rate and the environmental release rate is established for a number of antifouling coating types using data from a variety of available laboratory, field and calculation methods. Apart from a modified Dome method using panels, all laboratory, field and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 18 publications
(23 reference statements)
1
39
0
2
Order By: Relevance
“…In addition, tin concentrations in a TBT paint were also determined. The area concentrations were calculated using the CEPE mass-balance calculation method (Finnie, 2006), a method which is also accepted in the EU for estimating the release rate of biocides (reportworkshop-report, 2006). The method calculates the total area concentration of biocides in the dry antifouling paint and estimates the sum of a 14-d cumulative initial release and a steady-state release (mg/cm 2 /d) for the remainder of the specified lifetime by the use of Equations (1) and (2).…”
Section: Calculation Of Metal Concentrations In Commercial Antifoulinmentioning
confidence: 99%
“…In addition, tin concentrations in a TBT paint were also determined. The area concentrations were calculated using the CEPE mass-balance calculation method (Finnie, 2006), a method which is also accepted in the EU for estimating the release rate of biocides (reportworkshop-report, 2006). The method calculates the total area concentration of biocides in the dry antifouling paint and estimates the sum of a 14-d cumulative initial release and a steady-state release (mg/cm 2 /d) for the remainder of the specified lifetime by the use of Equations (1) and (2).…”
Section: Calculation Of Metal Concentrations In Commercial Antifoulinmentioning
confidence: 99%
“…It is a general practice to measure the leaching rate by the rotating cylinder test established by ISO1518-1 23) . However, it is also well known that the leaching rate measured by the ISO/ASTM method is often greater than the one expected for actual ship data 24,25) . If the leaching rate measured by the ISO/ASTM method was accurate under actual ship conditions, antifouling paints would disappear much earlier than the service period for a ship.…”
Section: Calculation and Resultsmentioning
confidence: 99%
“…As for the rotating cylinder tests, it has been found that D DAVID PUBLISHING the release rate is influenced by pH, dissolved ion content and the rotation speed of test cylinder [9]. However, the leaching phenomena of antifouling agents actually occurring in the ocean are considered to be much different from those observed in the laboratory tests [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the test method serves only as a guide for characterization of the early stage of the release as well as estimating the steady state leaching rate of antifouling ingredients from coatings. Further, it is stated in ISO (15181-1) that actual release rate of antifouling ingredients from ships' hull paints into the environment will depend on many factors such as ship operating schedules, length of service, berthing, conditions, paint condition, as well as temperature, salinity, pH, pollutants and bacterial effect [7,8].…”
Section: Introductionmentioning
confidence: 99%